Mycobacterial glycolipid Di-O-acyl trehalose promotes a tolerogenic profile in dendritic cells - Magallanes-Puebla, Alejandro (PLoS One, 2018)
Due to prolonged coevolution with the human being, Mycobacterium tuberculosis has acquired a sophisticated capacity to evade host immunity and persist in a latent state in the infected individual. As part of this evolutive process, mycobacteria have developed a highly complex cell wall that acts as a protective barrier. Herein we studied the effects of Di-O-acyl trehalose, a cell-wall glycolipid of virulent mycobacteria on murine bone marrow-derived dendritic cells. We have demonstrated that Di-O-Acyl-trehalose promotes a tolerogenic phenotype in bone marrow-derived murine DCs activated with mycobacterial antigens and Toll-like receptor agonists. This phenotype included low expression of antigen presentation and costimulatory molecules and altered cytokine production with downregulation of IL-12 and upregulation of IL-10, an anti-inflammatory cytokine. Additional markers of tolerogenicity were the expression of Indoleamine 2,3-dioxygenase and CD25. Furthermore, Di-O-Acyl-Trehalose promoted the expansion of FoxP3(+) regulatory T lymphocytes. A better understanding of mycobacterial cell-wall components involved in the evasion of immunity is a prerequisite to designing better strategies to fight tuberculosis.